Development of Guided Inquiry-Based Student Worksheet Assisted by Assemblr Edu to Enhance Conceptual Understanding in Electronics Course - Selviandri, Indah; Nehru, Nehru; Riantoni, Cicyn (Universitas Pendidikan Mandalika, 2025)
This study aims to develop a Guided Inquiry-Based Student Worksheet (LKPD) assisted by Assemblr Edu to improve studentsâ€™ conceptual understanding in an Electronics course. The LKPD is designed to engage students in structured investigative learning through the guided inquiry approach, while Assemblr Edu serves as a visualization tool for displaying 3D representations of equipment, materials, and electronic circuits used in learning activities. The study follows the ADDIE development model (Analysis, Design, Development, Implementation, and Evaluation), but is limited to the development phase. Data were collected through expert validation sheets and student perception questionnaires. The content and media experts each provided a validation score of 95%, categorizing the LKPD as â€œhighly validâ€ for field testing. Furthermore, the student perception analysis yielded a favorable score of 92.3%, indicating strong acceptance of the product in terms of design, content clarity, and learning motivation. These results confirm that the developed LKPD is both pedagogically and technologically suitable for use in higher education, particularly in supporting studentsâ€™ conceptual understanding of complex topics such as RC and RLC series circuits in alternating current (AC). The integration of guided inquiry with augmented reality enhances student engagement and allows for better conceptual visualization, making it a promising tool for improving the quality of Electronics instruction.